Biodiversity of Bacillus thuringiensis isolated from peruvian agroecosystem and evaluation of bioinsecticidal potential - Flores P, Abad (2011)
The biological control of pests & mites on peruvian agriculture was characterized by the intensive use of chemical pesticides. However, the decrease on yield and the emergence of resistance to pesticides have obligated to farmers to increase chemical pesticide use for plague control. This has caused environmental pollution, benefical insects death, persistence chemicals residues on fruits, acute and chronic toxicity risks, moreover an increase on production costs. The objectives of this research were to isolate and to characterize B. thuringiensis native strains, and) to evaluate entomotoxic potential against Spodoptera frugiperda. Were isolated 54 natives strains of Bacillus thuringiensis from peruvian agricultural soils. Microscopic morphology showed parasporal crystals characteristic of B. thuringiensis diversity. The strains were evaluated and confirmed with biochemistry and growing characteristic. The bioassays performed on Spodoptera frugiperda showed the strain BT-UNMSM-42 had the most efficient toxicity with 39,73% mortality to 50 μg/mL and 71,93% mortality to 250 μg/mL, with standard deviation 11,30 and 9,98; respectively.